Mobilność zawodowa nauczycieli w pierwszych latach Drugiej Rzeczypospolitej - Sanojca, Karol (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych Instytut Historyczny, 2020)
After Poland regained its independence in 1918, establishing a uniform educational system became an important issue. Significant differences in the structure and density of the school network caused a necessity of evening out those disproportions and disparities. One of the most significant problems was the shortage of teaching staff, evident particularly in the area of the former Russian and Prussian partition, as well as in Upper Silesia. Therefore, numerous teachers changed their place of living and workplace, encouraged by the opportunity to improve their financial situation, work in better organizational conditions or get promoted. They also responded to patriotic calls, moving to places where Polish presence had to be strengthened – especially the teachers from former Galicia (Austrian partition), where the situation regarding teaching staff was the best. Almost all of them had full teaching qualifications and were well-prepared for the profession, but often they had to acclimatize to different cultural environment and work among people who sometimes spoke dialects and were unfriendly to the newcomers. High professional mobility of the teachers mattered greatly in establishment and unification of Polish educational system. Only after several years of Polish independence, thanks to various in-service training courses and the development of teacher training colleges (then called “teacher seminaries” in Poland) the existent understaffing was alleviated.